Intermediate outcomes of a randomized trial of Tele‐Savvy: An online psychoeducation program: Dementia care research: Dementia care ‐ caregiving. (7th December 2020) - Hepburn, Kenneth; Griffiths, Patricia; Nocera, Joe R; Higgins, Melinda; Lindauer, Allison; Morhardt, Darby; Shah, Raj C; Epps, Fayron; Brewster, Glenna S; Bonds, Kalisha; Nash, Rachel
Abstract: Background: This presentation provides an intermediate report on the outcomes of the first twenty cohorts of family caregivers (N=220) engaged in a NIA‐supported randomized, three‐arm trial of Tele‐Savvy, a fully online version of the Savvy Caregiver, an evidence‐based in‐person psychoeducation program. Tele‐Savvy is specifically aimed at enhancing caregivers' capacity to manage the day‐to‐day challenges of caregiving by promoting caregiving mastery; the intended outcome is the reduction of caregiving distress. Tele‐Savvy engages groups of 5‐8 caregivers in 7 weekly synchronous online groups led by a trained facilitator; in between, caregivers are provided with 36 daily video lessons they can view whenever and as often as they wish. Caregivers were recruited in cohorts of 15 from 34 states and 2 Canadian provinces and randomly assigned (in a 2:2:1 ratio) to immediate participation in Tele‐Savvy, an attention control condition (Healthy Living), or usual care. Method: Data reported here were gathered on key outcomes at baseline and then 3 and 6 months. Multilevel mixed models were used to test for group, time, and group‐by‐time effects for each of the outcomes. Result: We found a significant group‐by‐time effect on CES‐D‐assessed caregiver depression (p<.001) with the active group showing significant decreases over time (p<.001). Of note, 35% of the active group reported clinically significant depression at baseline; this reduced to 22% by six months. In contrast, 25.5% those in the waitlist group scored as clinically depressed, a figure that increased to 33% by six months. We found a significant group‐by‐time effect on caregiver perceived strain (p<.001) with the active group demonstrating significant reductions over time (p<.001) and the waitlist control group demonstrating significant increases (p=.010). Likewise, there was a significant group‐by‐time effect (p=.001) on caregivers' reactions to care recipient behaviors (RMBPC) with significant reductions over time among the active caregivers (p=.001). Caregiver competence demonstrated a significant group‐by‐time effect (p‐.009) with the active group demonstrating significant increases over time (p<.001). Findings regarding caregivers' management of the situation were comparable: a significant group‐by‐time effect (p=.003) with the active group demonstrating significant increases over time (p<.001). Conclusion: At this point, Tele‐Savvy appears to be achieving its aims of enhancing mastery and decreasing distress.